Anteseden Kepuasan Pelanggan: Kualitas Pelayanan, Profesionalisme Kerja, Promosi - Suyono, Joko; Sukaris, Sukaris; Saputra, Didin (Jurnal Mahasiswa Manajemen, 2022)
Abstract Background – for service companies such as banks, customer satisfaction is very vital and basically every company, especially service companies, always strive to improve customer satisfaction. High customer satisfaction can increase profits. For this reason, in this study, several factors are discussed which are antecedents of customer satisfaction. Objective - This study aims to analyze the effect of service quality, work professionalism, and service quality on customer satisfaction, either partially or simultaneously. Design / methodology / approach – the population in this study were customers of Bank Jatim Hospital Dr. Branch. Soetomo Surabaya with a total of 2,400 customers. The technique for determining the number of samples uses the Slovin formula and from a population of 2,400 customers, 96 customers are obtained as research samples. The sampling technique used random sampling with a lottery system. Data analysis was done by using multiple linear regression test. Findings – The results of the study show that service quality, work professionalism, and service quality affect customer satisfaction, either partially or simultaneously. Research implication – The results of this study can be used as a reference by companies, especially the banking industry to improve customer satisfaction by paying attention to antecedent factors in the form of service quality, work professionalism, and service quality. Limitations – The population of this research is limited to Bank Jatim, for generalization it is necessary to do research with a wider scope and involve several banks as the population.